Akibat Hukum Merger Bank Syariah Mandiri, BRI Syariah, dan BNI Syariah - Usak, Usak (Wajah Hukum, 2023)
The purpose of writing this article is to examine legal arrangements for merger of Islamic banking and legal consequences of the merger of Bank Syariah Mandiri, BRI Syariah, and BNI Syariah. The research method used in this research is normative juridical method. Results of this study found that provisions regarding the merger of Islamic Banking are carried out in accordance with the provisions of the legislation as mandated by Article 17 paragraph (3) of Law Number 21 of 2008 concerning Islamic Banking. The legal arrangements for the merger of Islamic Banking in Indonesia can be referred to the Banking Law, Limited Liability Company Law, Islamic Banking Law, Government Regulation Number 28 of 1999, and OJK Regulation Number 41 of 2019. In addition, the merger of Sharia Banks must also pay attention to terms and conditions relating to the prohibition of monopolistic practices and unfair business competition as referred to in Law Number 5 of 1999. The legal consequences of the merger of BRI Syariah, BNI Syariah and Bank Mandiri Syariah may affect the company, shareholders, customers and employee.